Communication Strategies of Startups During the Natural Catastrophe of the 2024 DANA: Impact on Public Opinion and Business Reputation - Rodríguez Vera, Ainhoa del Pino; Rando-Cueto, Dolores; Ruiz-Herrería, Minea; De-las-Heras-Pedrosa, Carlos (MDPI, 2025)
In October 2024, a DANA (Isolated Depression at High Levels) triggered torrential rains across the Valencian Community, causing 227 deaths, severe infrastructure damage, and economic losses estimated at €17.8 billion. In this context of crisis, startups, despite having fewer resources and less experience than large corporations, played a significant role in crisis communication, shaping public perception and operational continuity. This study explores the communication strategies adopted by startups during and after the disaster, focusing on their activity on Instagram, TikTok, and Facebook between October 2024 and January 2025. Using a mixed-methods approach, we conducted a quantitative analysis of digital discourse through the Fanpage Karma tool, assessing metrics such as engagement, reach, and posting frequency. Sentiment analysis was performed using GPT-4, an advanced natural language processing model, and in-depth interviews with startup representatives provided qualitative insights into reputational impacts. The findings reveal that startups which aligned their discourse with the social context, prioritizing transparency and emotional proximity, enhanced their visibility and credibility. These results underscore how effective crisis communication not only mitigates reputational risk but also strengthens the local entrepreneurial ecosystem through trust-building and social responsibility.
Keywords: Inundaciones - Valencia - En los medios de comunicación social; Redes sociales en internet; crisis communication; organisational resilience; Startups; start-up; reputation; social media; Valencia